Fillers Compounding and Process Optimization of Polyamide Wet-coating (Journal of Fiber Bioengineering and Informatics, 2018)
In view of the many problems in the coating of the trademark, such as the poor stability of the filler,\rthe poor adhesive resistance and ink absorption of the fabric, the high pH value and insufficient printing\rstability, etc. this paper focuses on the study of two kinds of common inorganic fillers, wollastonite and\rkaolin, on the structure of the polyamide 6 coating film and the properties of the wet coating trademark\rfabric. The mixture of these two kinds of filler is applied to the coating slurry, and the ratio and dosage\rare optimized. On this basis, combined with production practice, the wet coating process conditions\rwere optimized. The results showed that the mass ratio of wollastonite and kaolin is 1:1 (the mass of\rthe filler is 22% of anhydrous methanol), the compatibility of coating slurry is higher than that of the\rcoating slurry prepared from single wollastonite, it is not easy to settle, but also the dispersion of coating\rslurry is better than that of only kaolin, and the microporous structure on the surface of coating film\ris more uniform. Moreover, the coated fabrics presented higher ink absorption performance. When the\rcoating temperature is 35 \u25e6C, the viscosity of the coating is 2\u223c3 Pa\u00b7s, the baking temperature is 160 \u25e6C,\rand the baking time is 80 s. The color fastness to the soaping color of the coated fabric reaches to grade\r4-5, the printing effect reaches to 3-4, the whiteness and the fabric style are better.